Insulin Treatment Prevents the Increase in D-Serine in Hippocampal CA1 Area of Diabetic Rats. (March 2015) - Yang, Jing; Song, Yang; Wang, Hongxin; Liu, Chunna; Li, Zhongzhe; Liu, Ying; Kong, Yawei
Purpose: Diabetes is a high risk factor for dementia. Employing a diabetic rat model, the present study was designed to determine whether the content ofd -serine (d -Ser) in hippocampus is associated with the impairment of spatial learning and memory ability. Methods: Diabetes was induced by a single intravenous injection of streptozotocin (STZ). The insulin treatment began 3 days after STZ injection. Results: We found that both water maze learning and hippocampal CA1 long-term potentiation (LTP) were impaired in diabetic rats. The contents of glutamate, d -Ser, and serine racemase in the hippocampus of diabetic rats were significantly higher than those in the control group. Insulin treatment prevented the STZ-induced impairment in water maze learning and hippocampal CA1-LTP in diabetic rats and also maintained the contents of glutamate, d -Ser, and serine racemase at the normal range in hippocampus. Conclusions: These results suggest that insulin treatment has a potent protection effect on CA1-LTP, spatial learning and memory ability of the diabetic rats in vivo . Furthermore, insulin may take effect by inhibiting the overactivation of N -methyl-d -aspartate receptors, which play a critical role in neurotoxicity.